The Scintillation Counters of the High-Energy Particle Detector of the China Seismo-Electromagnetic (CSES-02) Satellite - Simona Bartocci; Roberto Battiston; Stefania Beolè; Franco Benotto; Piero Cipollone; Silvia Coli; Andrea Contin; Marco Cristoforetti; Cinzia De Donato; Cristian De Santis; Andrea Di Luca; Floarea Dumitrache; et al. (Remote Sensing, 2024)
The High-Energy Particle Detector (HEPD-02) is one of the scientific payloads of the China Seismo-Electromagnetic Satellite (CSES-02). The HEPD-02’s main purpose is to characterize the particle environment in the Earth’s vicinity, identifying sudden changes in the fluxes and correlating them with solar and terrestrial phenomena. Additionally, HEPD-02 also has capabilities in detecting Gamma-Ray Bursts. At the core of HEPD-02, a tower of scintillation counters made of plastic and LYSO crystals is able to recognize electrons in the range between 3 and 100 MeV, protons and nuclei between 30 and 200 MeV/n. Plastic scintillators covering the calorimeter on five sides allow to reject particles entering from the top and not completely absorbed within its volume. In this work, the design of the HEPD-02 is reviewed in comparison to its predecessor, HEPD-01, highlighting the innovations of the new design. The design of each scintillation counter type has been fully validated through a campaign of prototype realization, testing, and characterization. The production of the scintillation counters, including the PMT selection process, is also discussed. Finally, the performance of the counters is compared with simulations, showing an agreement of within 20% with the expected performance, thereby meeting expectations.